Telaah Strategi Dakwah yang Efektif Secara Komunikatif dari Akun Instagram @penting_ngaji_ melalui Perspektif Teori Etika - Muhammad Izzul Muttaqin; Moh. Amiruddin; Evi Nurhalimah3 (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study examines the da'wah strategy employed by the Instagram account @penting_ngaji_, which features a question-and-answer (Q&A) approach to fiqh issues based on trusted Islamic reference books (mu'tabarah). Amid the rise of digital da'wah content that often emphasizes sensationalism and virality, this account presents a model of da'wah that is respectful, scholarly, and ethical. The aim of this research is to explore how this account has developed an effective da'wah strategy that communicates effectively while remaining grounded in Islamic moral principles. The research uses content analysis of 20 video reels published between February 1 and June 1, 2025. Each piece of content is analyzed based on communication style, use of references from Islamic texts, message structure, and ethical values reflected in the delivery of the da’wah. The analysis applies communication ethics theories, specifically deontological and teleological approaches. The deontological approach focuses on the moral duties and principles involved in delivering da’wah, while the teleological approach emphasizes the outcomes achieved from the da’wah delivery, particularly in terms of achieving beneficial goals for the audience. The findings show that @penting_ngaji_ has successfully developed a value-based preaching model that is adaptable to social media, without compromising the substance and ethics of the da’wah. This model uses simple, logical language grounded in trusted Islamic texts, addressing relevant issues faced by Muslims today. The study is expected to contribute to the development of higher-quality digital da’wah, serving as a reference for digital preachers to maintain ethics and the validity of religious sources in the modern era. It emphasizes the importance of ensuring that da’wah remains consistent with authentic Islamic teachings, even when delivered through digital platforms that often prioritize speed and popularity.